Photodynamic therapy of a 2-methoxyestradiol tumor-targeting drug delivery system mediated by Asn-Gly-Arg in breast cancer - Shi J (Dove Medical Press, 2013)
Jinjin Shi, Zhenzhen Wang, Lei Wang, Honghong Wang, Lulu Li, Xiaoyuan Yu, Jing Zhang, Rou Ma, Zhenzhong ZhangSchool of Pharmaceutical Sciences, Zhengzhou University, Zhengzhou, People's Republic of ChinaAbstract: Fullerene (C60) has shown great potential in drug delivery. In this study we exploited modified fullerene (diadduct malonic acid-fullerene-Asn-Gly-Arg peptide [DMA-C60-NGR]) as an antitumor drug carrier in order to build a new tumor-targeting drug delivery system. We also investigated the synergistic enhancement of cancer therapy using photodynamic therapy (PDT) induced by DMA-C60-NGR and 2-methoxyestradiol (2ME). Cytotoxicity tests indicated that DMA-C60-NGR had no obvious toxicity, while our drug delivery system (DMA-C60-2ME-NGR) had a high inhibition effect on MCF-7 cells compared to free 2ME. The tumor-targeting drug delivery system could efficiently cross cell membranes, and illumination induced the generation of intracellular reactive oxygen species and DNA damage. Furthermore, DMA-C60-2ME-NGR with irradiation had the highest inhibition effect on MCF-7 cells compared to the other groups. DMA-C60-NGR combined with 2ME showed a good synergistic photosensitization effect for inhibiting the growth of MCF-7 cells, demonstrating that DMA-C60-2ME-NGR may be promising for high treatment efficacy with minimal side effects in future therapy.Keywords: fullerene, drug delivery system, photodynamic therapy, tumor targeting